Souls under siege stories of war, plague, and confession in fourteenth-century Provence - Archambeau, Nicole (Cornell University Press, 2021)
Souls Under Siege -- Contents -- List of Illustrations -- Acknowledgments -- List of Abbreviations -- A Note on Names -- Introduction: Telling Stories of Danger in Fourteenth-Century Provence -- 1. Bertranda Bertomieua and the Death of King Robert of Naples, 1343 -- 2. Bishop Philippe Cabassole and the "War of the Seneschals," 1347-1349 -- 3. Master Nicolau Laurens and the Mercenary Invasion of 1357-1358 -- 4. Lady Andrea Raymon and the Great Companies, 1361 -- 5. Master Durand Andree and the Sacrament of Penance as a Moment of Danger -- 6. Sister Resens de Insula and the Desire for Certainty -- Conclusion: Lord Giraud de Simiana and the Health of Body and Soul -- Notes -- Bibliography -- Index